Effects of potassium fertilizer application on Qiongzhuea tumidinod shoots nutritional quality and soil nutrients - Li, Weidong; Dong, Wenyuan; Zhong, Huan; Fu, Tingxuan; Duan, Jixia; Sun, Jianye; Wu, Yiyuan (Frontiers in Plant Science, 2025)
IntroductionThe effects of potassium fertilization on the quality of Qiongzhuea tumidinoda shoots and soil nutrients were investigated by using a completely randomized block design with no fertilization as the blank control group (CK). In order to provide aiming to establish a theoretical foundation for optimizing cultivation practices and fertilization strategies in Q. tumidinoda forests.MethodsThe effects of four different levels of potassium fertilizer application [K1 (75 kg/ha), K2 (150 kg/ha), K3 (225 kg/ha), K4 (300 kg/ha)] on different nutrients (ash, crude fiber, protein, crude fat, soluble sugar, starch) and amino acid content of Q. tumidinoda shoots and soil nutrient content were studied.ResultsThe application of potassium fertilizer significantly reduced the ash content of Q. tumidinoda shoots but had no significant effect on crude fiber content. However, it significantly influenced soluble sugar, starch, and protein levels, which exhibited an initial increase followed by a decrease. K3 treatment had the highest soluble sugar content, K2 treatment had the highest starch content, and K3 treatment had the lowest crude fat content. There was no significant difference in the content of essential amino acids between different treatments, but the application of potassium fertilizer significantly affected other amino acid components, especially significantly promoted the accumulation of umami amino acids and sweet amino acids, indicating that the application of potassium fertilizer improved the umami and sweet taste of Q. tumidinoda shoots. With the increase of potassium application rate, the contents of soil organic matter, total nitrogen and total potassium increased first and then decreased, while the content of total phosphorus increased continuously. In the 0~20 cm soil layer, the highest contents of soil organic matter, total nitrogen, total phosphorus, total potassium, hydrolyzed nitrogen, available phosphorus and available potassium were K2, K1, K4, K1, K2, K2 and K1 treatments, respectively. In the 20~40 cm soil layer, the highest contents of soil organic matter, total nitrogen, total phosphorus, total potassium, hydrolyzable nitrogen, available phosphorus and available potassium were K2, K1, K4, K2, K4, K3 and K1 treatments, respectively.DiscussionAppropriate application of potassium fertilizer can not only improve the nutritional quality of bamboo shoots, but also significantly improve the content of soil organic matter and nitrogen, phosphorus and potassium nutrients. The optimal application amount of potassium fertilizer in this study was K2 treatment, that is, 150 kg/ha.